IL LINGUAGGIO POLITICO DELLE DONNE NEL RECENTE FEMMINISMO ITALIANO - Rossetti, Sandra (2015)
This study takes the ideas of two renowned 20th century political philosophers, as its reference point: Simone Weil and Hannah Arendt. They were among the first scholars to speak up in a man’s world. The study will try to shed some light on how political thought and gender were intertwined during the last century. We will thus try to understand whether a feminine language exists, which is able to pierce through a politics that has always been based on hierarchy and domination, as feminists claimed. By following this path - where women have been active in recent decades - the study will highlight the key words and will detect their echo (or their absence) in the language through which the recent women’s movements became the protagonists of Italian politics.